Fluks Metana dan Karakteristik Tanah pada Beberapa Macam Sistem Budidaya - , Suprihati; Iswandi Anas; Supiandi Sabiham; Gunawan Djajakirana (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2006)
Methane (CH4) is an important greenhouse gas that has a high heat trapping capacity thus potentially contribute to the global-warming. Agriculture is considered among the responsible emission sources of CH4. Relationship among soil characteristics, soil microbes, and CH4 flux is very important in understanding the mechanism involved in the mitigation effects of certain agriculture practices. Results of this research showed that rice field produced the highest CH4 flux (7.4976 ± 0.5299 mg CH4-C m-2 h-1, n=3), while vegetable, sweet potato, yam bean and corn cropping produced lower CH4 flux (-0.7708 ± 0.6434 to 0.4605 ± 0.5255 mg CH4-C m-2 h-1, n=3). Nitrifier population among cropping systems was 3.13x103 to 3.17x104 MPN g-1 soil (dry weight), while denitrifier population was 3.77x103 to 1.17x105 MPN g-1 soil (dry weight). There were no specific dominance proportion of nitrosomonas, nitrobacter, denitrifier and total propagule among cropping systems. The CH4 flux had highly correlation to soil water content (r = 0.951), soil pH (r = 0.852) and soil Eh (r = -0.982). Denitrifier had significantly correlation to soil pH (r = -0.635) and soil ammonium content (r = -0.681). Key words : CH4 flux, cropping system, soil characteristic, soil microbes